(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The article is devoted to the analysis of the influence of the Internet and digital technologies on the development of modern Russian speech. In the digital age, language is actively changing under the influence of new forms of communication, such as social networks, messengers, blogs, and online platforms. The study examines the features of Internet communication, including the emergence of new words and borrowings, the use of abbreviations, emojis, memes, and other elements of digital interaction. Special attention is paid to the transformation of written language norms, the simplification of grammar, and changes in stylistic characteristics of language in the online environment. The article also analyzes the impact of the digital environment on the culture of verbal communication and the formation of new linguistic habits among users, especially among young people. It concludes that the Internet not only contributes to the emergence of new linguistic phenomena but also has a significant influence on the development and dynamics of the modern Russian language, expanding its expressive capabilities and forming new forms of communication.